2016
DOI: 10.1016/j.dsr.2016.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Assessing microbial processes in deep-sea hydrothermal systems by incubation at in situ temperature and pressure

Abstract: At deep-sea hydrothermal vents, a large source of potential chemical energy is created when reducing vent fluid and oxidizing seawater mix. In this environment, chemolithoautotrophic microbes catalyze exergonic redox reactions which in turn provide the energy needed to fuel their growth and the fixation of CO 2 into biomass. In addition to producing new organic matter, this process also consumes compounds contained both in vent fluid and entrained seawater (e.g. H 2 , NO 3-). Despite their biogeochemical impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(98 citation statements)
references
References 52 publications
7
90
1
Order By: Relevance
“…However, our rates are similar to Mandernack and Tebo (1999) who cite short incubation times (≤ to our study) as an explanation for higher rates. Therefore, the short timescale of incubations and maintenace of deep-sea pressure and temperature (McNichol et al, 2016) probably explains why carbon fixation rates reported here are consistently higher than most other studies.…”
Section: 4contrasting
confidence: 53%
See 4 more Smart Citations
“…However, our rates are similar to Mandernack and Tebo (1999) who cite short incubation times (≤ to our study) as an explanation for higher rates. Therefore, the short timescale of incubations and maintenace of deep-sea pressure and temperature (McNichol et al, 2016) probably explains why carbon fixation rates reported here are consistently higher than most other studies.…”
Section: 4contrasting
confidence: 53%
“…In this study, we addressed these limitations by incubating subseafloor microbial communities with nitrate, oxygen, and hydrogen amendments (which are depleted by microbial activity upon sampling (McNichol et al, 2016)) as well as a 13 CO 2 label (to track carbon fixation). Microbes were maintained at in situ pressure and temperature for ≈ 24 h using isobaric gas-tight samplers (25MPa; McNichol et al, 2016;Seewald et al, 2002).…”
Section: 2mentioning
confidence: 99%
See 3 more Smart Citations